Jauja - Mortensen, Viggo 1958- (Soda Pictures, 2015)
"A remote military outpost in Patagonia, 1882, during the so-called ĐConquest of the DesertĐ, a genocidal campaign against the aboriginal population of the region. Acts of savagery abound on all sides. Captain Gunnar Dinesen has come from Denmark with his fifteen year-old daughter to take an engineering job with the Argentine army. Being the only female in the area, Ingeborg creates quite a stir among the men. She falls in love with a young soldier, and one night they run away together. When he wakes up the Captain realises what has happened and decides to venture into enemy territory to find the young couple. Jauja is the story of a manĐs desperate search for his daughter, a solitary quest that takes us to a place beyond time, where the past vanishes and the future has no meaning." (Covertext)